Comparação do cultivo celular 2D versus 3D em linhagem de adipócitos viscerais humanos tratados com irisina sobre os efeitos do pseudo SARS-COV-2 - Rocha, Paula Barreto da [UNESP] (2024)
Introduction: Since the beginning of the COVID-19 pandemic, there has been a collective effort aimed at understanding the behavior of the SARS-CoV-2 virus and, thus, developing effective treatments; however, the literature on the relationship between the virus and adipose tissue is scarce. Obesity is among the biggest negative prognostic factors given its chronic pro-inflammatory characteristic. Irisin, an endogenous myokine produced during physical exercise, can influence viral infection in obese individuals. Although monolayer (2D) cell culture studies are the standard for preclinical studies, three-dimensional (3D) culture is more similar to the in vivo environment, enabling the development of new drugs that more faithfully mimic the repercussions of the various possible interactions. Comparison of techniques can enable the development of reproducible studies. Objective: To compare 2D and 3D cell cultures of human visceral adipocyte lineage treated with irisin and infected by Pseudo SARS-CoV-2. Materials and Methods: Monolayer (2D) and three-dimensional (3D) cell cultures of human visceral pre-adipocytes were used to carry out the study, consisting of 4 groups: Control Group (C): adipocytes without treatment; ACE2 Group: adipocytes treated with Angiotensin- Converting Enzyme-2 (ACE2), ACE2+PV Group: adipocytes treated with SARS-CoV-2 pseudovirus (PV) and ACE2+I+PV Group: adipocytes treated with 20nM irisin for 24h and with Pseudo SARS-CoV-2. In these cell cultures, the uptake of fluorescence levels for Pseudo SARS-CoV-2 and ACE2 was measured. Results: Irisin treatment promoted a decrease in pseudo SARS-CoV-2 uptake levels for 2D (G3, 48796±321 vs G4, 44801±328) and 3D (G3, 51540±214 vs G4, 47027±165) in both cell culture models. For all differences, p<0.001 was observed. Conclusion: 3D culture of human visceral adipocytes showed similar results to those of monolayer culture, suggesting that both techniques can be used in future studies.